LEKSIKON FLORA DAN FAUNA PADA PERIBAHASA MINANG: KAJIAN EKOLINGUISTIK - Jambak, Mellinda Raswari; Al Anshory, Abdul Muntaqim (Balai Bahasa Provinsi Daerah Istimewa Yogyakarta, 2024)
The relationship between humans and their environment, especially flora and fauna, produces a language in the form of proverbs. The Minang tribe has its own proverbs that have a relationship with the surrounding nature. The formation of these proverbs is none other than because of human relationships with the surrounding environment. This research aims to describe (1) the category and grammatical form of flora and fauna lexicons in Minang proverbs, (2) the metaphorical dialog model of Minang proverbs containing flora and fauna lexicons, and (3) the praxis dimension of Minang proverbs containing flora and fauna lexicons. This research employs ecolinguistics theory as an analytical tool. Ecolinguistics is a term resulting from the combination of two words, ecology and linguistics. The term refers to the study of languages in relation to their environmental contexts. Primary data sources come from interviews with one of the leaders of the Jambak tribe in Malalo, West Sumatra. Meanwhile, other data sources come from journals and books relevant to the research. The research used qualitative methods. In collecting data, researchers used interview and note-taking techniques. While data analysis techniques, researchers used the Miles and Huberman model, namely data reduction, data exposure, and conclusion drawing. The result of this research is that there are flora and fauna lexicons from nine Minang proverbs. Flora lexicons are rice, weeds, cikarau, anau, and mingkudu. Fauna lexicons such as kabau, monitor lizard, bilalang, mancik, and ula. These ten lexicons are in the form of nouns and root words. There are three aspects of the environment or TOPOS: space, place and time. These three aspects have certain patterns and references. The praxis dimension in Minang proverbs is recorded in three praxis dimensions, namely the idological dimension (the Minang tribe's understanding of the flora and fauna lexicon), the social dimension (the relationship between the Minang people and nature), and the biological dimension (describing the biological characteristics of the flora and fauna lexicon).Hubungan manusia dengan lingkungan khususnya flora dan fauna menghasilkan sebuah bahasa berupa peribahasa. Suku Minang memiliki peribahasa tersendiri yang memperlihatkan hubungan mereka dengan alam sekitarnya. Pembentukan peribahasa tersebut tidak lain karena hubungan manusia dengan lingkungan sekitarnya. Penelitian ini bertujuan untuk mendeskripsikan (1) kategori dan bentuk gramatikal dari leksikon-leksikon flora dan fauna dalam peribahasa Minang, (2) model dialog metafora peribahasa Minang yang mengandung leksikon flora dan fauna, dan (3) dimensi praksis peribahasa Minang yang mengandung leksikon flora dan fauna. Penelitian ini menggunakan teori ekolinguistik sebagai pisau analisis yang merupakan hasil penggabungan dua kata, yakni ekologi dan linguistik. Istilah itu mengacu pada pengkajian terhadap bahasa-bahasa yang terkait dengan lingkungan. Sumber data primer berasal dari hasil wawancara dengan salah satu pemuka suku Jambak di Malalo, Sumatera Barat. Sedangkan sumber data lainnya berasal dari jurnal dan buku yang relevan dengan penelitian. Penelitian menggunakan metode kualitatif. Dalam pengumpulan data, peneliti menggunakan teknik wawancara dan catat. Pada analisis, peneliti menggunakan model Miles dan Huberman, yaitu reduksi data, pemaparan data, dan penarikan kesimpulan. Adapun hasil dari penelitian ini ialah terdapat sembilan leksikon flora dan fauna dari sembilan peribahasa Minang. Leksikon flora, yaitu padi, ilalang, cikarau, anau, dan mingkudu. Leksikon fauna seperti kabau, biawak, bilalang, mancik, dan ula. Sembilan leksikon ini berupa nomina dan kata dasar. Terdapat tiga aspek lingkungan atau TOPOS yaitu ruang, tempat, dan waktu. Tiga aspek ini memiliki pola-pola dan acuan tertentu. Adapun dimensi praksis dalam peribahasa Minang terekam dalam tiga dimensi praksis, yaitu ideologis (pemahaman suku Minang terhadap leksikon flora dan fauna), sosiologis (hubungan masyarakat Minang dengan alam), dan biologis (menggambarkan ciri-ciri biologis dari leksikon flora dan fauna).